2004
DOI: 10.1111/j.1538-7836.2004.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene expression and production by human LPS‐stimulated mononuclear cells are inhibited by sulfated heparin‐like semi‐synthetic derivatives

Abstract: Summary. Background: The K5 polysaccharide obtained from Escherichia coli strain 010:K5:H4 is a polymer of the disaccharidic unit formed by D-glucuronic acid and Nacetylglucosamine. This structure is akin to N-acetylheparosan, the precursory polymer of heparin and of heparan sulfate. This structural affinity with N-acetylated heparin and with desulfated heparin makes the K5 polysaccharide extremely useful for the preparation of sulfated heparin-like semi-synthetic derivatives. It has been demonstrated that hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
(38 reference statements)
3
28
0
Order By: Relevance
“…Heparin binds a number of cytokines and has been reported to decrease the inflammatory response of a variety of cell types, including endothelial cells (11,18,20). Besides directly blocking H. somnus adherence to BBEC, heparin pretreatment of BBEC also reduced the stimulatory effect of TNF-␣ on H. somnus binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin binds a number of cytokines and has been reported to decrease the inflammatory response of a variety of cell types, including endothelial cells (11,18,20). Besides directly blocking H. somnus adherence to BBEC, heparin pretreatment of BBEC also reduced the stimulatory effect of TNF-␣ on H. somnus binding.…”
Section: Discussionmentioning
confidence: 99%
“…4, a 1-hour preincubation of BBEC with TNF-␣ (100 ng/ml) more than doubled the number of adherent H. somnus after a 1-or 4-h incubation, compared to control BBEC. Heparin has been reported to have antiinflammatory properties, possibly due in part to its ability to bind various cytokines (11,18,20). To test whether heparin both inhibits TNF-␣ activation of BBEC and decreases H. somnus adherence to activated BBEC, we added heparin during either the TNF-␣ activation stage of the experiment or while TNF-␣-activated BBEC were incubated with H. somnus.…”
Section: Resultsmentioning
confidence: 99%
“…The heparin binding interaction may retain IL-6, IL-8, and MCP-1 close to its sites of secretion that may favor a paracrine mode of activity [37, 38]. However, the soluble form of heparin sulfate may diminish the expression and production of inflammatory cytokines [39]. Chondroitin sulfate proteoglycans mainly present in the extracellular matrix may retain the cytokines such as IL-6 in the extracellular matrix and protect for further inflammation [40].…”
Section: Resultsmentioning
confidence: 99%
“…[15]. The presence of O-sulphated glucuronic acid residues, not detectable in extractive heparin, and the conformational change induced by the enzymatic modification of K5 by C5-epimerase enable its strong anti-inflammatory activity, as shown in a rat model of carrageenan-induced pleurisy [18] and in human LPS-stimulated mononuclear cells [16]. Our group has also demonstrated that the K5 derivative K5-N,OSepi protects the brain against I/R injury [17].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their extent and pattern of sulphation, chemically sulphated K5 derivatives have been shown to possess different degree of antithrombotic/anticoagulant activity. As previously described [16], the semi-synthetic glycosaminoglycan K5 polysaccharide derivative K5-N,OSepi was obtained by N-desacetylation/N, O-sulphation of K5 polysaccharide and epimerization of K5 with the enzyme glucuronyl C5 epimerase. This compound has been demonstrated to be endowed with anti-inflammatory and anti-adhesive effects, but it is devoid of any anti-coagulant activity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%